Space, Language and Identity Politics in Higher Education (Journal of Student Affairs in Africa, 2021)
As a way of introducing the theme tackled by this guest-edited issue of the Journal of Student Affairs in Africa (JSAA), it is worthwhile to pose a question, albeit a rhetorical one: Why would a journal dedicated to theoretical, practical and reflective contributions on student affairs entertain a special issue on space, language and identity politics in higher education?An answer to this may be found in an exposition by Benedict Anderson (2006) in Imagined Communities. Anderson argues:Communities are to be distinguished, not by their falsity/genuineness, but by the style in which they are imagined. (Anderson, 2006, p. 7).